Improved liver lipid catabolism and utilization in growth hormone transgenic common carp (Cyprinus carpio L.) through enhanced lipolytic and fatty acid β-oxidation pathways - Wu, Yunya; Li, Rui; Wu, Xingxing; Guo, Wei; Li, Yongming; Song, Yanlong; Tao, Binbin; Chen, Ji; Han, Dong; Xie, Shouqi; Wang, Yaping; Zhu, Zuoyan; et al. (Frontiers in Endocrinology, 2022)
Growth hormone (GH) transgenic common carp (Cyprinus carpio L.) show desirable aquaculture traits. Their specific growth rate (SGR) and feed efficiency (FE) are approximately 12% and 17% higher than the wild-type (WT) common carp, respectively. However, the mechanisms of lipid catabolism (lipolysis and fatty acid β-oxidation) and utilization in GH transgenic common carp are still unclear. In this study, we firstly compared the lipid metabolism of GH transgenic (initial weight 3.72 ± 0.32 g) and WT (initial weight 3.30 ± 0.28 g) common carp fed with a normal fat level diet (6% lipid, 33% protein) for two months, then compared the growth performance of GH transgenic (initial weight 3.65 ± 0.33 g) and WT (initial weight 3.27 ± 0.26 g) common carp fed with different fat levels diets (6% lipid and 12% lipid, 33% protein) for two months. We found that the lipid content in serum, liver and whole body was significantly reduced in GH transgenic common carp, the hepatic activities of the lipolytic enzymes hormone-sensitive lipase and adipose triglyceride lipase were enhanced, and the hepatic expression level of hormone-sensitive lipase was upregulated. In addition, the mitochondrion numbers were increased, and the expression level of carnitine palmitoyltransferase-1a and carnitine palmitoyltransferase-1b was upregulated in the liver of GH transgenic common carp. GH transgenic common carp showed higher weight gain and SGR than that in WT carp when fed with a normal-fat diet as they did with a high-fat diet, and GH transgenic common carp showed higher FE than that in WT carp when fed with a high-fat diet. These results suggested that the lipid metabolism and utilization was improved in the GH transgenic common carp liver through enhanced lipolytic and fatty acid β-oxidation pathways. Our study provides new insights into improving lipid utilization in some aquaculture fish species.